A novel study on thermal enhancement in the flow of magnetized ternary hybrid nanofluid toward an elastic surface with nonlinear heat generation - Riaz, Muhammad; Khan, Nargis; Hashmi, Muhammad Sadiq; Rezapour, Shahram; İnç, Mustafa (Wiley-V C H Verlag Gmbh, 2025)
Ternary hybrid nanofluids are excellent at efficiently transferring heat for solar systems, electronics, and industrial operations because they combine three nanoparticles in a base fluid. Their diverse range of uses includes biomedical therapies, oil recovery, catalysis, and thermal energy storage. Recently, ternary hybrid nanofluids have replaced more traditional hybrid nanofluid flows in an effort to improve heat transmission. In the present study, the thermal performance of magnetized ternary hybrid nanofluid flow toward an elastic porous surface has been investigated in the presence of thermal radiation and nonlinear heat generation. The effects of an induced magnetic field have also been taken into account. The ternary hybrid nanofluid is made up of the suspension of three different nanoparticles that is, copper (Cu), silicon dioxide (SiO2), and iron oxide (Fe3O4) in base fluid Kerosene oil. The leading PDEs of the proposed model have been altered to ODEs by introducing suitable similarity variables. The obtained system of ODEs along with the boundary conditions has been numerically solved by using a bvp4c solver. The motion of ternary hybrid nanofluid declines in the presence of the magnetic field. The induced magnetic parameter and reciprocal magnetic Prandtl number weaken the induced magnetic profile. The existence of thermal radiation and nonlinear heat generation is significant in enhancing the thermal performance of ternary hybrid nanofluid. The volume fraction of solid nanoparticles boots up the heat transfer rate. A novel thermal enhancement is observed in the flow of ternary hybrid nanofluid as compared to hybrid nanofluid. The use of ternary hybrid nanofluid is quite advantageous in achieving desired heat transmission rates rather than hybrid nanofluid.
Keywords: Radiation